KAJIAN FITOKIMIA DAN PROKSIMAT TEPUNG KULIT PISANG MUSA SAPIENTUM DAN UJI ORGANOLEPTIKNYA PADA DONAT - Aryani, Titin; Mu'awanah, Isnin Aulia Ulfah; Widyantara, Aji Bagus (PERSATUAN AHLI GIZI INDONESIA, 2020)
All types of banana peel can be processed into flour. This study aims to conduct phytochemical and proximate studies of Musa sapientum banana peel flour and its organoleptic test on donuts. The research is quantitative. Phytochemical and proximate profiles were obtained from the results of laboratory tests, while the organoleptic profile of banana skin flour in making donuts was obtained from the results of donut acceptance tests on 60 panelists. The phytochemical profiles examined were antioxidant activity, anthocyanin and carotene levels. The organoleptic profile of Musa sapientum banana peel flour in making donuts examined was taste, color, texture, and aroma. Proximate profiles examined were water, ash, fat, protein, carbohydrate, fiber and yield content. The results showed that the antioxidant activity of Musa sapientum banana peel flour was 61.26 percent, anthocyanin levels 15.62 mg/100g, carotene 136.61 ppm, water content 6.92, ash content 1.89 percent, fat content 2.82 percent, protein content 5.31 percent, carbohydrate content 73.98 percent, fiber content 40.58 percent and yield 40.05 percent. Organoleptic profile of Musa sapientum donut banana flour with 25 percent of banana peel flour substituent on a scale of 1-5, taste parameters obtained values of 4.37, color 3.36, texture 3.54, aroma 3.68. The conclusion of the research is donuts made from Musa sapientum banana peel flour with 25 percent substituents of banana peel flour having a relatively good phytochemicals, proximate and organoleptic profile on donuts.